2020
DOI: 10.1371/journal.pone.0236150
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between frontal knee position and the degree of thoracic kyphosis and lumbar lordosis among 10-12-year-old children with normal body weight

Abstract: Introduction Incorrect positioning of the body in space increases the tension of the myofascial tissue and overloads the skeleton. It is important to look for factors that affect the deterioration of body posture that could be eliminated. Understanding the interrelationship between the positioning of individual body segments should be the key knowledge for those involved in the prevention and correction of faulty body posture. The study aimed to determine the relationship between the degree of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The GMS of children with DS are consistently low compared to those of normal children, and the largest difference is seen in relation to balance [23]. Balance is one of the major factors that affect the safety and independence skills of children with DS, and is the most difficult function to acquire.…”
Section: Motor Skills In Pediatric Patients With Down Syndromementioning
confidence: 99%
“…The GMS of children with DS are consistently low compared to those of normal children, and the largest difference is seen in relation to balance [23]. Balance is one of the major factors that affect the safety and independence skills of children with DS, and is the most difficult function to acquire.…”
Section: Motor Skills In Pediatric Patients With Down Syndromementioning
confidence: 99%
“…Exercise can improve poor body posture in those without obesity, but it is even more important for those with obesity because, along with directly improving body posture, it can help to reduce weight, which will, in turn, improve body posture. Moreover, exercise has a direct effect on the increase in body energy expenditure and the acquisition of motor skills, ameliorates of cardiovascular and metabolic profile, and contributes to reduce weight gain with positive effects on posture [ 109 , 110 , 111 ].…”
Section: Therapeutic Exercise Benefits For Incorrect Body Posturementioning
confidence: 99%
“…In fact, several studies have shown that with age, body posture issues more seriously compromise metabolism, including cardiopulmonary function and the skeletal system [ 110 ]. Indeed, previous studies have shown that many adolescents are sitting for long periods during school time, which leads to a muscular imbalance of their trunk muscles [ 111 ].…”
Section: Therapeutic Exercise Benefits For Incorrect Body Posturementioning
confidence: 99%